Effect of Inoculation of Microsymbiont on the Teak Seedlings at Nursery Stage - Shedage, S. M.; Patil, N. S.; Tadel, M. B.; Patel, D. P. (Indian Forester, 2015)
Seedlings of Tectona grandis L. were planted under different salinity levels, viz. normal soil (<4 ECe soil), saline soil (4-8 ECe) and highly saline soil (8-12 ECe) and seedlings were inoculated with azetobactor + arbuscular mycorrhizal (AM) fungi, azospirillum + varbuscular mycorrhizal (AM) fungi and combination of all three. Experiment was repeated for two years and data recorded at the end of each experiment on nutrient content in different plant parts (leaves, stem and root), chlorophyll content, root colonization and survival per cent. Triple inoculation (azetobactor+ azospirillum+AM) significantly influenced on the nutrient status and survival per cent of teak seedlings as compared to uninoculated seedlings under salt condition, which was followed by dual inoculation of Azospirillum and VAM.